The political economy of the African pharmaceutical sector's “industrial underdevelopment” lock-in: The importance of understanding the impact of persistent colonial extractive institutions - Banda, Geoffrey (Frontiers in Research Metrics and Analytics, 2023)
Improved African pharmaceutical manufacturing has been on global and local agendas since the 1970s, yet the industry has been locked-in into low technologies for decades. What caused the technological and industrial stagnation for such a critical sector for local and global health security? What are the political economy roots of such long-running industrial underdevelopment lock-in? What do colonial extractive economic and political institutions and their setup and mixes have to do with the sector? This study considers how extractive economic and political institutions' architectures and infrastructures shaped the African pharmaceutical industry's underdevelopment. We argue that extractive economic and political institutions shaped contemporary institutions in former colonial countries, and these institutions persist for a long time. The pivotal argument of innovation systems is that technological change-driven innovation is important for building superior economic performance and competitiveness, and institutions are a vital component of the system. However, institutions are not value-neutral; they carry the political and economic objectives and aspirations of the agents who design them. Innovation systems theory needs to incorporate the analysis of extractive economic and political institutions and the role they played in locking-in the African pharmaceutical industries into underdevelopment.